Readers' advisory service in the public library - Saricks, Joyce G. (ALA editions., 2005)
In public libraries, reference librarians are often called on to make recommendations to readers, sometimes in genres that they don't personally read. Learning how to frame a discussion and articulate the appeal of a book, author, or genre marks the essence of a successful readers' advisor. Readers' advisory is defined as, "patron-oriented library service for adult leisure readers," according to Saricks, a noted expert on the subject. In the completely revised third edition of Readers' Advisory Service for Public Libraries, Saricks updates this critically acclaimed how-to guide, making it more.